Amino acids and acylcarnitine production by Chlorella vulgaris and Chlorella sorokiniana microalgae from wastewater culture - Ballesteros Torres, Juan Manuel; Samaniego Moreno, Luis; Gómez Flores, Ricardo Alberto; Tamez Guerra, Reyes Silvestre; Rodríguez Padilla, María Cristina; Tamez Guerra, Patricia (PeerJ Inc., 2019)
Production of amino acids and acylcarnitine by Chlorella vulgaris and Chlorella sorokiniana was determined after 13 d of culture in wastewater, under various culture conditions. Wastewater was collected from ‘‘La Encantada’’ stream, located in Saltillo, Coahuila, Mexico. Microalgae was cultured at 23◦C and natural day light, including the use of the following conditions: (1) extra light (12:12 light:dark cycles, 1,380 lumens), (2) agitation (130 rpm), and (3) both conditions, until exponential phase. Supernatant products were then analyzed by liquid chromatograph coupled to mass spectrometry. In addition, metabolomic profiles related to growing conditions were evaluated.